Biomimetic three-dimensional microenvironment for controlling stem cell fate - Zhang, Hu (The Royal Society, 2011)
Stem cell therapy is an emerging technique which is being translated into treatment of degenerated tissues. However, the success of translation relies on the stem cell lineage commitment in the degenerated regions of interest. This commitment is precisely controlled by the stem cell microenvironment. Engineering a biomimetic three-dimensional microenvironment enables a thorough understanding of the mechanisms of governing stem cell fate. We review the individual microenvironment components, including soluble factors, extracellular matrix, cell–cell interaction and mechanical stimulation. The perspectives in creating the biomimetic microenvironments are discussed with emerging techniques.